Do Genetic Markers of Inflammation Modify the Relationship between Periodontitis and Nonalcoholic Fatty Liver Disease? Findings from the SHIP Study. (November 2017) - Akinkugbe, A.A.; Avery, C.L.; Barritt, A.S.; Cole, S.R.; Lerch, M.; Mayerle, J.; Offenbacher, S.; Petersmann, A.; Nauck, M.; Völzke, H.; Slade, G.D.; Heiss, G.; et al.
An association between periodontitis and nonalcoholic fatty liver disease (NAFLD) has been reported by experimental animal and epidemiologic studies. This study investigated whether circulating levels of serum C-reactive protein (CRP) and a weighted genetic CRP score representing markers of inflammatory burden modify the association between periodontitis and NAFLD. Data came from 2, 481 participants of the Study of Health in Pomerania who attended baseline examination that occurred between 1997 and 2001. Periodontitis was defined as the percentage of sites (0%, <30%, ≥30%) with probing pocket depth (PD) ≥4 mm, and NAFLD status was determined using liver ultrasound assessment. Serum CRP levels were assayed at a central laboratory, and single-nucleotide polymorphisms previously identified through genome-wide association studies as robustly associated with serum CRP were combined into a weighted genetic CRP score (wGSCRP ). Logistic regression models estimated the association between periodontitis and NAFLD within strata of serum CRP and separately within strata of the wGSCRP . The prevalence of NAFLD was 26.4% (95% confidence interval [CI], 24.6, 28.1) while 17.8% (95% CI, 16.0–19.6) had ≥30% of sites with PD ≥4 mm. Whereas the wGSCRP was not a modifier ( P interaction = 0.8) on the multiplicative scale, serum CRP modified the relationship between periodontitis and NAFLD ( P interaction = 0.01). The covariate-adjusted prevalence odds ratio of NAFLD comparing participants with ≥30% of sites with PD ≥4 mm to those with no site affected was 2.39 (95% CI, 1.32–4.31) among participants with serum CRP <1 mg/L. The corresponding estimate was 0.97 (95% CI, 0.57–1.66) for participants with serum CRP levels of 1 to 3 mg/L and 1.12 (95% CI, 0.65–1.93) for participants with serum CRP >3 mg/L. Periodontitis was positively associated with higher prevalence odds of NAFLD, and this relationship was modified by serum CRP levels.